Strategi Impression Management Petugas Public Relations dalam Management Citra: Studi Kasus Pada Kanwil Kemenhumkam Kepulauan Riau - Kintan Maharanie Putri; Nurrahmawati (UNISBA Press, 2022)
Abstract. District office of Ministry of Justice and Human Rights Kepulauan Riau is one of Indonesia Government’s institution that administers laws and human rights, where such things considered to be uncommon in society. Aside that, this institution has achieved several accomplishments for their works, for example: achievement for their public services in 2021 from Ombudsman, Best JDIHN Management in category district office in Pembinaan Satuan Kerja menujunWBK/WBBM in 2020. The main discussion in this research was about to understand the role of public relations officer in District office of Ministry of Justice and Human Rights Kepulauan Riau towards the process of establishing the strategy aspect in impression management, as well as public relations officers’ strategy in managing the institution’s image, and the reason behind the strategy strategy’s implementation. This research uses qualitative method with study case approaches. The theory that used for this research is impression management theory by Erving Goffman. This research focused on the research questions as a guide in conducting a deep interview towards five informants that work as public relations officer in District office of Ministry of Justice and Human Rights Kepulauan Riau. The result of this research shows that impressions management strategy were formed by showing self presentation through the way they dress, but aside that self presentation were also presented through arranging personality and professionalism as a second aspect. Public relations officer strategy uses three strategies with different aims for each strategy. But the sole aim of their strategy is to implement their strategies in order to create appropriate impressions, strategy to establish a competent impression, and strategy to establish integrated impression with a good morality. The reason behind the strategy that were taken up is to create appropriate impressions, to establish a competent impression, and to establish integrated impression with a good morality. Abstrak. Kanwil Kemenhumkam Kepulauan Riau merupakan kementerian dalam Pemerintah Indonesia yang membidangi urusan hukum dan hak asasi manusia yang mana masyarakat masih awam dengan jenis pekerjaan ini. Selain itu, banyaknya penghargaan yang diraih seperti penghargaan pelayanan publik tahun 2021 dari Ombudsman, pengelola JDIHN (Jaringan Dokumentasi dan Informasi Hukum Nasional) terbaik I, terbaik Ke-2 dalam Kategori Kanwil dalam Pembinaan Satuan Kerja menuju WBK/WBBM tahun 2020. Pokok bahasan dalam penelitian ini mengenai peran public relations Kanwil Kemenhumkam Kepulauan Riau terhadap proses pembentukan konsep dan kesan yang ingin disampaikan kepada oranglain dengan mengungkapkan aspek strategi pengelolaan kesan yang dibentuk, strategi petugas public relations dalam mengelola citra perusahaan, dan alasan strategi tersebut diimplementasikan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teori yang digunakan dalam penelitian ini adalah teori impression management dari Erving Goffman. Penelitian ini memfokuskan dengan menggunakan pertanyaan penelitian sebagai panduan melakukan wawancara mendalam kepada lima informan sebagai petugas public relations di Kanwil Kemenhumkam Kepulauan Riau. Hasil penelitian ini adalah strategi pengelolaan kesan yang dibentuk dengan menunjukkan penampilan diri melalui cara berbusana, adapun menetapkan kepribadian dan sikap profesionalitas yang kemudian strategi petugas public relations menggunakan tiga strategi yaitu melalui pengimplementasian strategi untuk memperoleh kesan disukai, strategi untuk memperoleh kesan kompeten, dan strategi untuk memperoleh kesan berintegritas dan moral yang baik. Alasan strategi tersebut diimplementasikan untuk mendapatkan kesan disukai, kesan berkompeten, dan kesan berintegritas dan layak secara moral.